2020
DOI: 10.25077/ar.7.2.109-117.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Illocutionary Speech Acts in Colloquial by Anak Dalam Jambi Tribe

Abstract: Anak Dalam Jambi Tribe (ADJT) lives in the forest, far from the population, and the existence is rare. This research aims to determine whether ADJT uses illocutionary speech act, function, and type of speech act used. This research uses qualitative with pragmatic research type. The data is in the form of an illocutionary speech act, which is then transcript by putting out the conversation context. This research’s data source is from ADJT, who lives in Merangin Regency, Jambi Province, Indonesia. Result researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Pendapat responden memberikan pandangan bahwa masih cukup yakin menggunakan bahasa Serawai di lingkungan tempat tinggal mereka, walaupun bersinggungan langsung dengan bahasa lain, hal ini juga yang membuat bahasa Serawai masih eksis di kalangan pengguna khususnya masyarakat yang sejak lahir menggunakan bahasa Serawai dan di besarkan pada lingkungan bahasa Serawai tanpa ada sentuhan bahasa lain, situasi ini sejalan dengan (Prastio et al, 2023) yang mengatakan bahwa eksistensi masyarakat Suku Anak Dalam Jambi dalam merawat lingkungan dan budaya karena penggunanya memiliki ideologi, biologi, sosiologi, dan budaya.…”
Section: Tabel 2 Lingkungan Pengguna Bahasa Serawaiunclassified
“…Pendapat responden memberikan pandangan bahwa masih cukup yakin menggunakan bahasa Serawai di lingkungan tempat tinggal mereka, walaupun bersinggungan langsung dengan bahasa lain, hal ini juga yang membuat bahasa Serawai masih eksis di kalangan pengguna khususnya masyarakat yang sejak lahir menggunakan bahasa Serawai dan di besarkan pada lingkungan bahasa Serawai tanpa ada sentuhan bahasa lain, situasi ini sejalan dengan (Prastio et al, 2023) yang mengatakan bahwa eksistensi masyarakat Suku Anak Dalam Jambi dalam merawat lingkungan dan budaya karena penggunanya memiliki ideologi, biologi, sosiologi, dan budaya.…”
Section: Tabel 2 Lingkungan Pengguna Bahasa Serawaiunclassified
“…It is greatly realized about the application of language function that leads to speech acts (Widya, 2017). Moreover, It is considered in each aspect of life, as well as having different world of context gives impacts to illocutionary (Prastio, 2020). Second, based on the problem worldwide especially Corona-viruses (Covid-19) Joe Biden as president-elect United States America 2020 speech about covid19.…”
Section: Introductionmentioning
confidence: 99%
“…It is due to the delivering of information related to the importance of being part of public health during this day that she was concerned about. In the same year, Prastio et al (2020) identified the use of illocutionary acts in colloquial ways by the Anak Dalam Jambi Tribe. They found the directive, expressive and comimsive acts used by anak dalam Jambi Tribe.…”
Section: Introductionmentioning
confidence: 99%